2010
DOI: 10.1002/elps.201000077
|View full text |Cite
|
Sign up to set email alerts
|

Successive multiple ionic polymer layer coated capillaries in the separation of proteins – Recombinant allergen variants as a case study

Abstract: A successive multiple ionic polymer layer (SMIL) coating consisting of two pairs of poly(diallyldimethylammonium chloride) and dextran sulfate (DS) layers was applied for the separation of recombinant products of the major birch pollen allergen Betula verrucosa (Bet v 1a). The combination with volatile ammonium bicarbonate buffer at pH 6.70 offers the possibility for future MS hyphenation. The negative net charge of allergens required DS as terminal SMIL layer. The EOF was accelerated from 3.17x10(-8) m(2) V(-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…The former capillary coatings can be produced simply by flushing the capillary with solutions of highly adsorptive agents. Very stable and uniform adsorbed coatings can be produced by applying multiple layers of oppositely charged polymers, as indicated for the first time by Katayama et al [20, 21] and demonstrated by others subsequently [2229]. …”
Section: Introductionmentioning
confidence: 99%
“…The former capillary coatings can be produced simply by flushing the capillary with solutions of highly adsorptive agents. Very stable and uniform adsorbed coatings can be produced by applying multiple layers of oppositely charged polymers, as indicated for the first time by Katayama et al [20, 21] and demonstrated by others subsequently [2229]. …”
Section: Introductionmentioning
confidence: 99%
“…ammonium acetate and ‐formate (data not shown). Based on the facile degassing at pH 6.5, the related pH drift and the screening results (data not shown), an initial pH of 8.0 was selected for subsequent optimization of NG and SL flow rates.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, only one CZE-UV separation has been reported in this context to date [10], although CZE seems predestined for this task since it can equally address minute changes in the protein net charge and the conformation [24][25][26][27]. The applicability of various CE-UV modes, such as CZE, CIEF, and affinity CIEF, for the characterization of modified recombinant allergens has been described previously [28][29][30][31][32]. In comparison with UV, MS detection exhibits a higher sensitivity and allows for a further confirmation of identity by mass information of intact allergen variants.…”
Section: Introductionmentioning
confidence: 99%
“…Protein adsorption was observed on fused silica capillary and on PB/DS by the increase of layer thickness, while no increase could be measured for PB or PB/DS/PB coatings [17]. SMIL coatings based on two pairs of PDADMA/DS have been used for the separation of recombinant allergen variants in ammonium bicarbonate buffer at pH 6.7 with excellent repeatability/reproducibility [18]. PDADMA/PSS SMIL could be also deposited on poly(methyl methacrylate) microchip [19].…”
Section: Introductionmentioning
confidence: 98%